Coupling effects of barge motion and sloshing. (1st August 2017) - Su, Yan; Liu, Z.Y.
Abstract: A rectangular barge with partially filled rectangular tank is considered. The sloshing motions in tank and coupling motions of floating body are discussed in both frequency domain and time domain. In frequency domain, the superposition of natural sloshing modes is adopted for modelling liquid sloshing in tank and eigen-functions expansion is used for the motions of barge. In time domain, nonlinear Boussinesq-type approach in terms of velocity potential is used for simulating internal liquid motions. An impulse response function is introduced for solving the motions of floating body and the hydrodynamic coefficients in the equations of motions are obtained from the results in frequency domain. The quadratic damping term in roll is taken into account for both numerical approaches. The numerical results in both frequency domain and time domain are compared with experimental results in basin.